Superimposed zinc and gold mineralization in the Dunde iron deposit, western Tianshan, NW China: Constraints from LA-ICP-MS fluid inclusion microanalysis - Li, Hengxu; Zhang, Zhaochong; Liu, Bingxiang; Jin, Yilun; Santosh, M.; Pan, Junyi (Ore geology reviews, 2022)
[Display omitted] •We report single fluid inclusion compositions by LA-ICP-MS from Dunde iron deposit.•The ore fluids related to zinc mineralization originate from granitic magma.•Zinc and gold mineralization do not share the same ore system with Fe deposit. The submarine volcanogenic iron oxide (SVIO) deposits are one of the most important sources of high-grade iron ores in China. Many large- and medium-scale SVIO deposits were recently discovered in the Awulale metallogenic belt (AMB) in Western Tianshan, NW China. The Dunde deposit in the AMB is a unique iron deposit containing large-scale Zn and medium-scale Au resources. The zinc mineralization in this deposit is generally located at the margin of iron orebodies constituting composite iron-zinc orebodies. To clarify the genetic relation between iron and Zn with Au mineralization, we conducted a detailed investigation of sphalerite-hosted fluid inclusions in the Dunde deposit. The primary fluid inclusions in sphalerite are liquid-rich, with homogenization temperature in the range of 189–219 ℃, and salinity of 19.68–22.38 wt% NaCl equiv. Single fluid inclusion LA-ICP-MS analysis suggests a magmatic source for the fluid as reflected by high Rb/Na (0.001–0.016), K/Na (0.18–0.83) and low Ca/K (1.03–9.38) ratios, which are distinctly different from those of basinal brines. The Cs/(K + Na + Ca)*10000 values (6.0–13.4) of sphalerite-hosted fluid inclusions are equivalent to those in porphyry-type Cu-Mo deposit (4.7–23.8), indicating that the ore-forming fluid originated from a highly evolved granitic magma, rather than intermediate-mafic magmatism related to iron mineralization. Thus, we propose that the zinc and gold mineralization in the Dunde deposit might be products of superimposed mineralization on iron orebodies during hydrothermal alteration related to granitic intrusions.